Implementation of E-Learning Model Assisted Interactive Video in Increasing Motivation and Learning Achievment on Application Letter Material In Class Xii IPS 1 Madrasah Aliyah Negeri 1 Banjarmasin Academic Year 2020/2021 - Mariani Mariani; mariani mariani (Universitas Islam Negeri Alauddin, 2021)
This research studies about the Â the implementation ofÂ E-learning model assisted by interactive video media to overcome the low motivation and learning achievment of class XII IPS 1 MAN 1 Banjarmasin on application letter material. This research aims at finding out the urgence and effectivity of using E-Learning model assisted by interactive video in teaching-learning process. This study used a classroom action research design (PTK) with 2 cycles. Each cycle consists of planning, implementing actions, observing and evaluating, and analyzing and reflecting. The subjects in this study were students of class XII IPS 1 with a total of 31 students. Data collected using observation techniques, written tests and questionnaires. Furthermore, the data were analyzed using quantitative descriptive analysis techniques and qualitative analysis. The results showed that there could be an increase in learning outcomes from 62.47 in cycle I to 80.26 in cycle II, an increase in student motivation from 78.55 in cycle I to 105.5 in cycle II and students responded well to implementation. e-learning assisted by interactive video media.